2015
DOI: 10.1109/tcad.2015.2413848
|View full text |Cite
|
Sign up to set email alerts
|

Fault-Tolerant Topology Generation Method for Application-Specific Network-on-Chips

Abstract: As the technology sizes of integrated circuits (ICs) scale down rapidly, current transistor densities on chips dramatically increase. While nanometer feature sizes allow denser chip designs in each technology generation, fabricated ICs become more susceptible to wear-outs, causing operation failure. Even a single link failure within an on-chip fabric can halt communication between application blocks, which makes the entire chip useless. In this paper, we aim to make faulty chips designed with network-on-chip (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(108 citation statements)
references
References 39 publications
1
107
0
Order By: Relevance
“…Because the previous works on link-failure-aware NoC topology generation did not consider the VFI regime, we evaluate the proposed method with FTTG [16] and mesh topology (MESH) by configuring a VFI environment that is the same as ours. With four multimedia applications, namely the VOPD, MPEG-4, D_38 [21], and H.264 with 64 nodes from MCSL [22], as benchmark, we evaluate the energy consumption, latency, and area using our cycle-accurate simulator based on SystemC by combining the simulation results from ORION 2.0 [23].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Because the previous works on link-failure-aware NoC topology generation did not consider the VFI regime, we evaluate the proposed method with FTTG [16] and mesh topology (MESH) by configuring a VFI environment that is the same as ours. With four multimedia applications, namely the VOPD, MPEG-4, D_38 [21], and H.264 with 64 nodes from MCSL [22], as benchmark, we evaluate the energy consumption, latency, and area using our cycle-accurate simulator based on SystemC by combining the simulation results from ORION 2.0 [23].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the methods for tolerating permanent link failures in regular topologies cannot be directly applied to custom topologies. Tosun et al proposed a fault-tolerant custom topology generation (FTTG) method with a mapping algorithm for application-specific NoC design to tolerate at least one link failure by detouring default routing path [16]. This study showed enhanced energy efficiency with reduced area overhead compared to the previous works by focusing on minimized extra routers and considering the number of cores and communication traffic patterns in mapping stage.…”
Section: Link-failure-aware Noc Designmentioning
confidence: 99%
See 3 more Smart Citations